Pengaruh Tingkat Implementasi IPSAS Berbasis Akrual Terhadap Transparansi Fiskal Pemerintah Pusat : Studi Komparatif Negara OECD, Non-OECD, BRICS - Muhamad Dimas Pangestu; Saring Suhendro (Ekonomi Keuangan Syariah dan Akuntansi Pajak, 2025)
This study aims to analyze the effect of the level of implementation of accrual-based International Public Sector Accounting Standards (IPSAS) on the fiscal transparency of the central government. In addition, this study also examines the differences in the level of IPSAS implementation among OECD, non-OECD, and BRICS countries. The study sample consisted of 20 countries selected through a purposive sampling technique based on three main criteria: (1) the central government has used accrual-based financial reports, either partially or fully; (2) the country has implemented IPSAS for more than five years; and (3) the country is listed in the Open Budget Survey. This study uses panel data covering the years 2015, 2017, 2019, 2021, and 2023. The independent variable in this study is the level of implementation of accrual-based IPSAS as measured by three main indicators: commitment to accruals, accrual reporting, and accrual policies. Meanwhile, the dependent variable, fiscal transparency, is measured using the Open Budget Index score, which reflects the level of openness of the central government budget to the public. The analysis was conducted using panel data regression with a random effects model approach. The results show that the level of accrual-based IPSAS implementation has a positive effect on fiscal transparency, but this effect is not statistically significant. However, there are significant differences in the level of IPSAS implementation among OECD, non-OECD, and BRICS countries. This finding indicates that IPSAS implementation in various countries is influenced by different institutional factors and fiscal capacities, thus requiring strong institutional support to promote more effective fiscal openness.